2021
DOI: 10.3389/fcell.2021.661747
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous Recurrent Mutations Inducing Dysfunction of ROR2 Gene in Patients With Short Stature

Abstract: PurposeROR2, a member of the ROR family, is essential for skeletal development as a receptor of Wnt5a. The present study aims to investigate the mutational spectrum of ROR2 in children with short stature and to identify the underlying molecular mechanisms.MethodsWe retrospectively analyzed clinical phenotype and whole-exome sequencing (WES) data of 426 patients with short stature through mutation screening of ROR2. We subsequently examined the changes in protein expression and subcellular location in ROR2 caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…To date, pathogenic variants of the ROR2 receptor have been associated with Brachydactyly B (OMIM # 113000) and Robinow syndrome (OMIM # 268310), in which some individuals show dental problems such as delayed eruption and delayed root formation of permanent teeth [ 37 ]. Recent findings indicate that heterozygous recurrent nucleotide alternations, including the p.Gly559Ser missense variant located within the ROR2 kinase domain, might also be associated with isolated short stature [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, pathogenic variants of the ROR2 receptor have been associated with Brachydactyly B (OMIM # 113000) and Robinow syndrome (OMIM # 268310), in which some individuals show dental problems such as delayed eruption and delayed root formation of permanent teeth [ 37 ]. Recent findings indicate that heterozygous recurrent nucleotide alternations, including the p.Gly559Ser missense variant located within the ROR2 kinase domain, might also be associated with isolated short stature [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Demographic information, physical examination results and clinical symptoms were taken into account. Details of cohort were reported in the previous study ( 18 , 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…The most common cause of monogenic short stature is the deficiency of the short-stature homeobox-containing (SHOX) gene ( Marchini et al, 2016 ; Ponomarenko et al, 2020 ). A study revealed newer mechanistic insights that identified c.1675G > A mutation in receptor tyrosine kinase-like orphan receptor 2 (ROR2) in patients with short stature ( Gui et al, 2021 ). To date, key molecular mechanisms underlying stunted growth and childhood short stature remain equivocal.…”
Section: Introductionmentioning
confidence: 99%